The Cambridge handbook of formal semantics - Aloni, Maria; Dekker, Paul Jacques Edgar (Cambridge : Cambridge University Press, 2016)
Formal semantics - the scientific study of meaning in natural language - is one of the most fundamental and long-established areas of linguistics. This Handbook offers a comprehensive, yet compact guide to the field, bringing together research from a wide range of world-leading experts. Chapters include coverage of the historical context and foundation of contemporary formal semantics, a survey of the variety of formal/logical approaches to linguistic meaning and an overview of the major areas of research within current semantic theory, broadly conceived. The Handbook also explores the interfaces between semantics and neighbouring disciplines, including research in cognition and computation. This work will be essential reading for students and researchers working in linguistics, philosophy, psychology and computer science.
Title from publisher's bibliographic system (viewed on 04 Jul 2016).
Keywords: Semantics